Mapping the Intellectual Landscape of Islamic Educational Thought: A Global Bibliometric Study - Annisa Maryam Nurrohmah; Benny Prasetiya; Febry Suprapto; khoiriyah khoiriyah (PT. Caesarindo Triloka Persada, 2026)
This study presents a global bibliometric analysis of Islamic Educational Thought, aimed at mapping the intellectual landscape and exploring trends, contributions, and potential future directions of research in the field. Based on data from Scopus, this study examines the growth in the number of publications related to Islamic education from 2015 to 2025, with particular emphasis on research in Southeast Asia, particularly Indonesia and Malaysia. The research reveals a significant increase in publications, with a focus on digital education innovations, such as augmented reality, game-based learning, and social practice pedagogy, indicating a shift from traditional, normative approaches towards technology-driven, character-based educational models. This analysis also highlights the growing global importance of Islamic education in addressing key issues like anti-corruption education, Islamic character development, and madrasah management, linking these to the United Nations Sustainable Development Goals (SDG 4 and SDG 16).Through the use of bibliometric methods, including co-citation and network analysis, the study identifies the intellectual structure of the field, revealing an interdisciplinary shift involving the integration of biomedical, social, and psychological research. This dynamic evolution reflects the growing interconnectedness of various fields, suggesting that future research will increasingly focus on bio-socio-digital interconnectivity, where human development is viewed through the simultaneous interaction of biological, social, and digital factors. The study also emphasizes the need for a more integrated, systems-based approach in Islamic education, proposing a shift toward the adoption of a bio-psycho-social-epigenetic model in research. Ultimately, this paper provides a comprehensive overview of the current state of global research in Islamic education and sets the stage for future studies that focus on interdisciplinary, digitally-informed approaches to education.